Adaptive dynamics of the 5-HT systems following chronic administration of selective serotonin reuptake inhibitors: a meta-analysis - Fritze, Stefan; Spanagel, Rainer; Noori, Hamid Reza (Journal of neurochemistry, 2017)
Selective serotonin reuptake inhibitors (SSRIs) are the most frequently prescribed antidepressants. However, a major concern is their delayed onset of action, which is hypothesized to be associated with the time required for serotonin (5-HT) autoreceptors to desensitize, which should be reflected by actual neurochemical changes. Numerous in vivo microdialysis studies have been published that report on 5-HT levels in different brain sites following SSRI administration. Here, we performed a meta-analysis on dynamic changes of 5-HT neurotransmission during the course of chronic SSRI treatment. We conducted a meta-analysis on research articles of 5-HT neurotransmission measured by in vivo microdialysis in rat brain after subchronic and chronic SSRI administrations. In total, data from 42 microdialysis studies (798 rats) were analyzed. Within the first week of SSRI treatment, extracellular 5-HT concentrations drop in frontal cortex. Over the next 2 weeks of treatment, a linear increase in extracellular 5-HT levels up to 350% of prior treatment baseline is evident (n = 269). However, in hippocampus, prefrontal cortex, nucleus accumbens, and ventral tegmental area we found increased 5-HT levels within the first 3 days of SSRI administration. The time course of 5-HT dynamics in frontal cortex is in line with the hypothesis that 5-HT autoreceptors desensitize over 2-3 weeks of SSRI treatment and thereby enhanced extracellular 5-HT levels ensue. Yet, in other regions we did not find evidence supporting the traditional autoreceptor-mediated feedback loops hypothesis and thus other neurobiological adaptation mechanisms may also play a role in the delayed onset of SSRI action.